Pengembangan Paket Instruksional Dalam Rangka Meningkatkan Pengetahuan Mahasiswa Tentang Higiene Makanan dan Minuman - Syarifah Miftahul El Jannah (Universitas Negeri Jakarta, 2018)
Human Development Index (HDI) has three dimensions, Growth Development Product, enrollment rate, and life expectancy. Increasing life expectancy is determined by good health services, besides; human knowledge about food hygiene has a vital role as well. However, the latest has been neglected due to human ignorance. Therefore, it is required teaching or training materials which probably could improve human knowledge, especially about food and beverages hygiene. To what extent Instructional package based on problem solving development could improve effectively student’s knowledge about food and beverages hygiene is a research question for this study. As a class experiment, respondents were students of Program of Diploma IV Environmental Health Department, at Polytechnic of Health, Ministry of Health Jakarta II. Meanwhile, as the control class, respondents were students of Program of Diploma IV, at Polytechnic of Health Ministry of Health Bandung. There are three Instructional Packages have been developed and test used for measuring knowledge about food and beverages hygiene. There are five t-test have been conducted to verify the effectiveness of Instructional Packages. Research results indicate that there is a significant difference between mean of gain score obtained from post and pre test at treatment group compare to control group. Instructional package based on problem solving could be socialized to improving student’s knowledge about food and beverages hygiene.